Effectiveness of Integrated Teaching Among First MBBS Students - Supriya, Garapati; Ariyanachi; Mrudula, Chandrupatla (Journal of Current Scientific Research, 2024)
Introduction The arrangement of teaching content to relate to or unite concepts that are regularly taught in different academic courses or departments is referred to as integration of teaching. It simply refers to creating links between theoretical knowledge and actual application. Teaching the fundamental sciences in separate blocks prevents students from having the opportunity to connect and integrate their newly acquired knowledge. Objectives To evaluate the effectiveness of Integrated teaching method over traditional teaching and perception of students towards integrated method among first MBBS students Methodology The total of 62MBBS first year students are randomly divided into two groups, with 31 in each group. Group A is subjected for Conventional teaching and Group B for Integrated teaching method in the same topic. Among the 2 sessions one session is Horizontal and other is Vertical method of integrated teaching have been implemented. Finally, an evaluation test was conducted for both the groups and the mean marks obtained by the students were analyzed by using SPSS software version 17. Student’s perception towards this method was evaluated by pre-validated feedback questionnaire and analyzed. Results The mean marks (outof40) obtained by Group B (Conventional teaching) is 13.82 and by Group A (Integrated Teaching) is 31.18. So, the marks obtained by students after integrated method were found to be higher than the other group which underwent conventional teaching and this difference was found to be statistically significant (P <0.0001). Discussion and conclusion In comparison to the typical conventional method, integrated teaching has been found to be a more successful mode of instruction in terms of students' performance and assessment exams.
Keywords: Curriculum; Revision; Approach; Integration